Analyzing the influence of integrated café spaces on library user engagement through third place theory - Prijana, Prijana; Rahima, Marsya; Raquel Theresia, Gwina; Bifakhlina, Febriyanti (Faculty of Communication, Padjadjaran University, 2026)
Background: Modern libraries are evolving into multidimensional activity centers, focusing not only on providing information but also on comfort and social interaction. Younger generations such as Gen Z and Millennials view libraries as social spaces that blend academic activities with relaxation. One innovation introduced is the presence of cafés, which are part of the